Comparison of Different Student Categories using Augmented Reality and Conventional Methods - Sirat, Norfatanah; Othman, Maisara; A.A. Ayub, (Evolution in Electrical and Electronic Engineering, 2021)
This paper is about introduction to augmented reality (AR) technology for educational purposes whose aim is to provide a module education for students. AR can be defined as an interactive 3D environment which links physical reality and virtual reality. This technology is widely used in education that can help the students quickly acquire, process, and remember the information. The method that is usually used is unattractive and less efficient to gain knowledge among the students. This problem occurs due to lack of interactive platforms in which most of the generation kids are addicted to their smartphone. The main objective for this project is to design VKV and KVKK modules using augmented reality applications. Method to create the AR education platform was not that difficult with the help of many open source platforms such as Unity Real-Time Development Platform or known as Unity 3D, blender, Vuforia and etc. The new AR application called ReModAR has successfully developed for Android OS and been tested to four students with different education backgrounds and categories. Based on the results, Alicia was able to gain a higher percentage difference and recorded a faster answering time when using the AR application method for both  modules. Even though Amsyar gained the lowest percentage difference, he showed good improvement in result time taken between conventional and application methods by 50% for KVKK and 66% for VKV module. From this augmented reality applications, it provides a significant impact on students in terms of quick learning understanding and it helps the students to answer and memorize the words easily than using conventional method. The students also gave a positive response while learning and playing with this interactive apps. We hope by built this application it helps the students to enjoy the learning process in a fun way.